Do Financial Performance and Corporate Social Responsibility Disclosure Matter to Investors? Evidence from the Indonesian Energy Sector - Muliati Muliati; Kasmawati Kasmawati; Arung Gihna Mayapada; Haryono Pasang Kamase (AMCA, 2026)
This study examines the effect of financial performance measured through accounting profit and total asset turnover and corporate social responsibility (CSR) disclosure on the return of shares of energy sector companies listed on the Indonesia Stock Exchange from 2012 to 2023. Company size and leverage are included as control variables to obtain a more accurate estimate. Using 288 company year observations and applying quantum regression, the study provides a broader understanding of how explanatory variables behave at different levels of stock returns, especially in sectors known for their high capital intensity and exposure to commodity price fluctuations. These findings reveal that accounting earnings consistently have a positive and significant effect on stock returns at the 0.50 and 0.75 quantities, suggesting that profitability serves as a strong signal for investors, especially in companies with medium to high performance. In contrast, total asset turnover and CSR disclosures did not show significant effects across all quantiles, suggesting that operational efficiency and sustainability reporting are not key considerations for investors in the sector. The size of the company and leverage also did not show a significant influence, although their inclusion improved the quality of the model. Overall, the study highlights that investors in the energy sector respond to profitability indicators more strongly than information related to operations or sustainability.